Revisiting the Sectarian Milieu: Pre-Islamic Arab Cultural Agency in the Dialectical Formation of the Qur’an - Muslikhun (UIN Syarif Hidayatullah Jakarta, 2025)
The examination of the Qur'ān's origins and its relationship with pre-Islamic Arab culture remains a contentious issue, complicated by narratives rooted in Islamophobia and the politicization of identity. This study seeks to reassess John Wansbrough's theory of the “sectarian milieu” by incorporating neglected aspects of pre-Islamic Arab culture, examining the influence of local factors in the Islamization process, and deconstructing the binary of “external influence versus internal authenticity.” Using a qualitative interdisciplinary methodology, the study integrates analysis of Quranic texts, Jahiliyyah poetry, archaeological inscriptions, and cultural anthropology. The findings show that the Qur'ān emerged as a result of a dynamic synthesis between pre-Islamic Arabic heritage (including oral traditions, ḥaram rituals, and tribal values) and external Judeo-Christian influences. This conclusion challenges Wansbrough's theory, which isolates the Arab context, while revealing a theologically revised continuum of cultural heritage. The recommendations of this study underscore the need for a comprehensive approach in early Islamic studies that incorporates archaeological, philological, and socio-historical evidence to avoid polarizing narratives manipulated in identity-political discourse.